Answer:
1. -8,
2. 58
3. 0
4.
5. -14/8 or -1.75
Explanation:
1. You just plug in 8 for x into the g(x) equation
So, -(8)^2+7(8)= -8
2. You do the same thing you did for number one.
Plug in 13 for the h(x) equation
|2-4(13)|= 50
Then plug in -1 for the f(x) equation
-(-1)^2+7(-1)= -8
You then do as it says- subtract h(x) from f(x)
Which is 50-(-8) and you get 58.
(That subtraction sign turns into addition/ 2 negatives make a positive)
3. Same thing again.
Plug in what they gave you (3y-1) for X
8(3y-1)-9
You get 24y-17
You then subtract off the -17 and get 24y=17
Divide the 24 off and get y=17/24
Plug the Y back into the equation
8(3(17/24)-1)-9 and you get 0
*Im not a hundred percent sure I did this one right*
4. This is the same as number 3. Didn’t have time to solve this, but it’s the same steps as number 3 :)
5. This time they didn’t give you x so you set it up differently
Now you set the f(x) equation equal to -23
8x-9=-23
Add off the to the 23 to isolate the variable
8x= -14
Divide off the 8
X= -14/8 or -1.75
B/9 is your answer
have a good evening
Answer:
70, I think
Step-by-step explanation:
............................
The order that will result in a final output of -31 when the first input is 0 is as follows; Third → Second → Fourth → First
<h3>How to find the order?</h3>
First gives;
y = -2·x + 34 = 18
Second gives;
y = -x/3 - 10 = -38/3
Third gives;
= -24
Fourth gives;
y = (x - 2)² = 36
We have after several iterations;
Third gives,
= -24
Next we input into the second to get,
y = -(-24)/3 - 10 = 24/3 - 10 = 8 - 10 = -2
Next we input into the fourth to get,
y = ((-2) - 2)² = (-4)² = 16
Next we input into the first to get,
y = -2×16 + 34 = -32 + 34 = 2
Which gives the order as follows;
Third → Second → Fourth → First
Learn more about this concept here;
brainly.com/question/17444851
#SPJ1